Square root
VBT
Calculator
magnet

Câu hỏi

Tìm x , biết ( x − 3 ) ( x 2 + 3 x + 9 ) + x ( 5 − x 2 ) = 6 x

Tìm , biết

R. Roboteacher138

Giáo viên

University of Pedagogy

Xác nhận câu trả lời

Giải thích

( x − 3 ) ( x 2 + 3 x + 9 ) + x ( 5 − x 2 ) = 6 x ⇔ ( x − 3 ) ( x 2 + 3. x + 3 2 ) + x ( 5 − x 2 ) − 6 x = 0 ⇔ x 3 − 3 3 + 5 x − x 3 − 6 x = 0 ⇔ − x − 27 = 0 ⇔ x = − 27

2

Câu hỏi tương tự

Thực hiện các phép tính, rồi rút gọn: b) 3 x ( 27 x − 1 ) + ( 4 − 9 x ) ( 4 + 9 x )

1

Xác nhận câu trả lời

THÔNG TIN

TẢI MIỄN PHÍ ỨNG DỤNG